2019
DOI: 10.14738/assrj.69.7079
|View full text |Cite
|
Sign up to set email alerts
|

Millennials’ Career Decision-Making Difficulties (Cdmd) in Indonesian University Students

Abstract: Though millennial has unique characteristics as digital natives who prefer to interact with images, branded goods, to have idols and who are interested in modern technological utilization, studying their career decision-making difficulties (CDMD) is barely reported in Indonesia. To respond to such gap, the current report was designed to pattern the CDMD of both male (N = 120) and female (N = 140) undergraduate students in Indonesia. The instrument of the research was totally adopted from Gati et al's. (1996) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
1
1
1
Order By: Relevance
“…The above finding corroborates the result of Akpochafo (2020), which suggests that there was no gender difference in all the difficulty levels of career decision-making difficulties among secondary school students in Nigeria. The finding, however, disagrees with Murniarti and Siahaan (2019), whose finding revealed that male students had more problems in making their career choices, especially with regard to lack of information which showed in their work that more than half of the males did not receive enough information about the types of occupation they are to go in for.…”
Section: Discussioncontrasting
confidence: 63%
“…The above finding corroborates the result of Akpochafo (2020), which suggests that there was no gender difference in all the difficulty levels of career decision-making difficulties among secondary school students in Nigeria. The finding, however, disagrees with Murniarti and Siahaan (2019), whose finding revealed that male students had more problems in making their career choices, especially with regard to lack of information which showed in their work that more than half of the males did not receive enough information about the types of occupation they are to go in for.…”
Section: Discussioncontrasting
confidence: 63%
“…It may suggest that for most Indonesians, future careers were not introduced, therefore were not developed at young ages. In addition, it may also confirm research finding [45] which concluded that half of the Indonesian undergraduate students were facing problems in deciding what jobs to have. Formally, a career is introduced when students are in senior high school as they prepare to continue their studies at universities.…”
Section: Motivation To Pursue a Career In Teachingsupporting
confidence: 64%
“…For women, it also shows that a higher score of vocational identity reflects how they appear to be more confident about themselves. Furthermore, Murniarti and Siahaan (2019) study in Indonesia shows that male undergraduates have a problem in making career-related decisions in comparison to female undergraduates. Moreover, male undergraduates seem to have a problem in finding information regarding career choices where they are more prone to receive many unrelated information about career and their tendency to be influenced by unreliable sources from social media.…”
Section: Literature Reviewmentioning
confidence: 99%